Review of the genus Hypobarathra Hampson, 1905 (Lepidoptera, Noctuidae, Hadeninae) with description of a new species - Saldaitis, Aidas; Benedek, Balázs; Behounek, Gottfried (Zootaxa, 2016)
The present study was initiated upon finding an unknown Hypobarathra species during a collecting expedition to the higher regions of western Sichuan Province in China in 2015. The genus previously contained only two Palaearctic species with remarkably different external appearance and distribution pattern. Interestingly, all three species of Hypobarathra are adapted to completely different eco zones and habitats, which are discussed under each species. According to Hacker et al. (2002), the closest relatives of the genus are Melanchra Hübner, [1820] 1816 and Odontestra Hampson, 1905. This statement should be corrected, since Hypobarathra is forming a common clade with Melanchra, Ceramica Guenée, 1852 and Ebertidia Boursin, 1968, while Odontestra representing another lineage within the tribus Hadeninae.